The poetry of “Idris bin Al-Yaman al-Yabisi (died 470AH)”: (Stylistic study) - Udah, Khawla Abdulhameed; Hameed, Nidhal Mahdi (Al-Adab Journal, 2023)
This study seeks to highlight the stylistic features of an Andalusian poet, Idris bin Al-Yaman, and to occupy the aesthetic aspects of his poetic writings, through three topics: The first topic includes rhythmic via rhythmic methods used in his poetry such as external and internal rhythm structure. The appropriate language of poetic line and rhyme, as well as repetition and parallelism have been used in his poetry to enhance the rhythm. The second topic has been devoted to the synthetic structure of a question, an appeal, and the actual composition, which gave his poetry an aesthetic and artistic dimension. As for the third topic, it included the semantic structure and highlighting the role of the artistic image and its delivery to the audience in the best way. Idris used analogy, and metaphor to clarify his meanings and to give aesthetic character to his poetic texts. Finally, the research concluded with a conclusion, and then the sources and references.